Salary Determinants for Higher Institutions of Learning in Kenya - Muturi, Bernard; Ngare, Philip (My University, 2014)
There has been a debate over the years on which category of salary determinants best predicts an employee salary, that is, whether it is organizational characteristics or individual attributes. This study adopts a hybrid approach and seeks to examine the relationship between work experiences, level of education, job category, and employee’s salary. The findings of the study have shown that there is a strong relationship. In addition, we have constructed a salary determinant model for employees of higher institutions of learning in Kenya. The study has great significance to human resource practitioners, who would find the salary determination model very useful in their practice. The hybrid approach to salary determination will also provide a different academic and scholarly perspective to the study of salary determinants.
Keywords: Salary Determinants; Stepwise Multiple Regression; Level Of Education; Work Experience; Job Category; Organizational Characteristics And Individual Attributes